Incentivizing (and Disincentivizing) Mothers to Utilize Maternal Health Services: A Focus Group Study - Perez, Amihan (Archīum Ateneo, 2020)
Background. In ensuring access to maternal health services, various strategies toward safer health practices and improved health service delivery are important ingredients to eliminate avoidable maternal deaths. A recent household survey showed that access to antenatal care (ANC) (89%) and facility-based delivery (FBD) (82.4%) in the Eastern Visayas region is significantly high, despite the extensive damage to over 500 health facilities caused by Typhoon Haiyan in November 2013. Postpartum care (PPC), however, was relatively low (37.4%). As these findings needed further elaboration, a qualitative study using focus groups was conducted. Method. The focus groups method was utilized to elicit responses from the mothers, BHWs, and midwives to explain what contributed to the high ANC visits, high FBD, and low PPC. Sixteen focus groups were conducted in the local dialect (Waray and Cebuano), and all discussions were audio recorded. Focus groups data were transcribed and subsequently translated to English text, then reviewed and validated by socio-linguistic academics from the region. Other data sources included debriefing session reports and expanded field notes. Nvivo 10 software was used in the coding process and data management. The data analysis referred to the principles of thematic analysis. Results. The findings showed that incentives in the form of free maternal services and cash grants drive mothers to go to the health facility for antenatal care and facility-based deliveries. The free services were provided by PhilHealth (the country's social health insurance), while cash grants were awarded through the government's conditional cash transfer program and other community partners. Mothers were provided with some financial risk protection through these financial incentives. The disincentives came in the form of local ordinances, which prohibited home births. Penalties included fines for both mother and birth attendant when the mother was found to deliver outside the health facility. The unintended stigma, shame, and fear that developed in response to these ordinances also deterred home births. The significantly low use of PPC services in the health facility was attributed to the lack of advices given to mothers regarding the need for follow- up care after delivery. It is also noted that there are no incentives for PPC, which may contribute to its low rates. The role of the community health workers and midwives were to inform and educate the mothers on these incentives and disincentives. However, these incentives and disincentives are extrinsic motivators and are deemed insufficient to provide long-term impact. Conclusion and Recommendations. The implementation of the incentives and disincentives in Eastern Visayas has increased rates of ANC and FBD. The presence of these in the current environment has initially facilitated behavior change, shifting home births to facility births. However, we argue that financial incentives, with a lack of intrinsic motivation, may be insufficient to sustain long-term impact. Disincentives, in the form of local ordinances, forced mothers instead to seek care in facilities. Such an approach may eventually become less effective over time. Incentives and disincentives are both demand-side factors, and to sustain change, concurrent improvements in the supply end need to be implemented. The capacity of facilities to absorb the increased demand should be in place to provide positive experiences for mothers in the health facilities.